Con/tact in the love poems of Carol Ann Duffy - Ho, Frida Gaya (2016)
Romantic love is a constant in human experience. Whether requited or unrequited, sensitively communicated or thoughtlessly expressed, love is a familiar emotion often made the subject of writing. This dissertation seeks to answer the question, “How do we speak of love?” with reference to the love poems of Britain’s Poet Laureate, Carol Ann Duffy. Attempts at speaking of love are often characterised by the lovers’ struggle to translate their experiences from a non-semantic form into words. By examining Duffy’s love poems, I argue that poetic writing offers an appropriate outlet for lovers which follows from acts of love during their amorous encounters. I begin by defining con/tact, a concept I have constructed to refer to haptic encounters between lovers. The subsequent chapters of this dissertation refer closely to a range of Duffy’s love poems, so as to demonstrate how con/tact operates in the poetic register. All in all, this dissertation argues that the metaphors of con/tact in Duffy’s love poems constitute a re-vision of how love is conventionally spoken of in amorous writing.